Stimulation of Monetary Policy in the Real Economy - Panahov, F. (Управління економікою: теорія та практика, 2022)
In order to ensure normal production growth and maximum employment of the population, in practice such regulatory instruments of macroeconomic policy as budgetary-tax (fiscal) and monetary (monetary) ones are used.
Through these regulators of macroeconomic policy, it is possible to achieve the necessary results in the economic and social life of the country in a short time.
The timing of achieving such results is directly related to the rigidity of the application of these regulatory levers.
The more rigid their application, the shorter the time for obtaining the intended results becomes.
The best results in the field of financial stabilization are achieved when all these regulators are used in parallel (jointly), and at the same time this whole process is fully coordinated. Для забезпечення нормального зростання виробництва та максимальної зайнятості населення на практиці використовуються такі регулюючі інструменти макроекономічної політики, як бюджетно-податковий (фіскальний) та монетарний. Через ці регулятори макроекономічної політики можна за короткий час досягти необхідних результатів в економічному та соціальному житті країни. Терміни досягнення таких результатів безпосередньо пов'язані з жорсткістю застосування цих регуляторних важелів. Чим жорсткіше їх застосування, тим коротшим стає час для отримання очікуваних результатів. Найкращі результати у сфері фінансової стабілізації досягаються, коли всі ці регулятори використовуються паралельно (спільно), і при цьому весь цей процес повністю скоординований.